ETHICAL CHALLENGES OF COUNSELING IN THE DIGITAL ERA - Aizun Riski Safitri; Samsul Arifin (LP2M IAI Al-Khairat Pamekasan, 2025)
The development of digital technology has led to significant changes in guidance and counseling practices, particularly through the use of online media. Digital counseling offers greater accessibility and flexibility of services; however, it also presents complex ethical challenges. This article aims to analyze ethical challenges in counseling in the digital era and to examine the application of professional ethical principles in technology-based counseling services. The method used is a literature review by analyzing scientific sources, academic journals, books, and professional ethical codes relevant to the topic. The results indicate that the main ethical challenges of digital counseling include risks to confidentiality and data privacy, blurred professional boundaries between counselors and clients, limitations in counselors’ technological competence, and ethical dilemmas related to the use of social media and artificial intelligence. The application of professional ethical principles such as confidentiality, integrity, professional responsibility, competence, and client protection is essential to maintain the quality and professionalism of digital counseling services. This article concludes that professional ethics remain relevant and essential in digital counseling, although contextual adaptation, strengthening of digital ethical literacy, and the development of clear operational guidelines are required in line with technological developments.